QUALITY CONTROL OF LATHE PROCESS IN MK-II PROGRAM PT DIRGANTARA INDONESIA - NARULITA, RACHMANIA
PT Dirgantara Indonesia (PT DI) is a state-owned aeronautics company engaged in aviation industry. PT DI is currently in partnership with Airbus for supplying fuselage and tailboom for Super Puma Family or known as MK-II. As the requirement for the further partnership, PT DI needs to implement quality control system, specifically using Statistical Process Control (SPC) method. The machining area under the Detail Part Manufacture Division uses the ?????????? control chart controlling process. However, the use of the ?????????? control chart in the low-volume production process and high product variation is ineffective. This is proven by the outside diameter as one of key characteristics (KC) which does not have sufficient amount of data to construct a control chart. The machining area requires quality control method that is suitable to the characteristic of the production system. This research develops process control procedures using the Deviation from Nominal (DNOM) method. The DNOM control chart is able to accommodate various types of components produced from homogeneous processes in one control chart. The procedure development is focused on KC outside diameter manufactured at the work center horizontal CNC lathe machine. The construction of control chart begins with the selection of components that have similar machining process. Then the homogeneity of variance test is performed to prove the component dimensional homogeneity assumption. Furthermore, the transformation of data using the DNOM technique is done by subtracting measurement value and the nominal target value. To see the process conditions, DNOM values are mapped on the EWMA control chart. The patterns depicted on the control chart are analyzed using western electric rules to identify the process out of control. To restore an in-control condition, an out of control action plan (OCAP) is designed. Procedures for making control charts and executing out of control action plans are documented in the company’s Standard Operating Procedure (SOP).